The Effect of Organic fertilizers on Growth Quality of Sweat corn (Zea mays saccharata L) - Zulfikar, Aji; Tyasmoro, Setyono Yudo; Islami, Titiek (International Journal of Environment, Agriculture and Biotechnology, 2023)
The experiment was conducted to study the effect of organic waste from rice husk, corn straw and sugarcane leaves as compost for sweat corn growth. The experimental design used in the study was a factorial randomized block design with two factors (compost types and doses), nine treatments, and three replications, P1: rice straw compost; P2: sugarcane leaves compost; P3: corn straw compost then doses were D1: 7,5 t ha-1; D2: 15 t ha-1; D3: 23 t ha-1. The result showed that the compost types and dose treatments had a significant effect on the maize growth, including the height, leaf area Index, stem diameter, and dry weight on specific observations without any interaction. Besides, the treatments also affected the yield of corn production. The highest yield was found at 23 t ha-1 (D3) dose in all types of compost treatments. Meanwhile the highest to the lowest yields were, respectively, P3 (9,29 t ha-1), P1 (8,72 t ha-1), and P2 (8,00 t ha-1).